Incidence of acute kidney disease after receiving hematopoietic stem cell transplantation: a single-center retrospective study - Akira Mima; Kousuke Tansho; Dai Nagahara; Kazuo Tsubaki (PeerJ, 2019)
Background Previous reports have shown that acute kidney injury (AKI) is common after hematopoietic stem cell transplantation (HSCT), which is a crucial treatment for patients with hematological disorders. AKI could increase mortality and induce adverse effects including the development of chronic kidney disease. The incidence of AKI in association with HSCT reportedly varies significantly because several definitions of AKI have been adopted. Acute kidney disease (AKD) is a new concept that can clinically define both AKI and persistent decreases in glomerular filtration rate (GFR) state. We conducted a retrospective cohort study to determine the incidence of AKD after HSCT. Methods This study included 108 patients aged between 16 and 70 years undergoing HSCT. In this study, AKD included clinical condition of AKI or subacute decreases in GFR. AKI was defined according to the Kidney Disease: Improving Global Outcomes guidelines based on serum creatinine. However, urine output data were not included to define AKI because the database lacked some of these data. Comparisons were made between groups using the Mann–Whitney U test. Results Acute kidney disease occurred in 17 patients (15.7%). There were significant differences between the AKD and non-AKD with respect to ABO-incompatible HSCT (p = 0.001) and incidence of acute graft versus host disease (GVHD) after HSCT (p < 0.001). The 100-day overall survival of patients with AKD and without AKD after HSCT was 70.6% and 79.8%, respectively (p = 0.409). Discussion ABO-incompatible HSCT and acute GVHD after HSCT were risk factors for the incidence of AKD. However, we could not find a significant association between AKD after HSCT and mortality.